PENGARUH METODE PEMBELAJARAN ROLE PLAYING DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MENANGANI DOKUMEN KANTOR SMK NEGERI 1 PAYAKUMBUH - Emilda Amza; Mawardi Effendi (Program Magister Pendidikan Ekonomi (S2), 2015)
This study aims to determine (1) The difference learning outcomes in Handling Office Document taught using learning method Role Playing through Giving Task learning method. (2) The difference learning outcomes of learning Handle Office documents in high motivasion study and low motivation study, (3) The obtion of interaction between teaching methods and learning motivation on Handling Office document learning outcomes. This research was a quasi-experimental (quasi experiment) were carried out in number 1 vocational school of Payakumbuh. The sample in this study was 60 students consisting of 30 tenth grade students in third office administration major and 30 eleventh grade students in fourth office administration major. Motivating questionnaire and test results of learning handle office documents, were used to collect the samples. The Data were analyzed by using alisis variance (ANOVA). The results showed that: (1) The average of student learning outcomes taught using Role Playing method wqs higher than taught by giving task of learning methods, (2) The average learning outcomes of high motivation students was lower than low motivation strudents, (3) There was no interaction between the use of teaching methods and learning motivation on student learning outcomes. Based on the data analysis result above, it can be concluded that the Role Playing learning method can improve student learning outcomes in handle office documents learning.Key word : earning methods role playing; learning methods administration tasks; student learning outcomes; students' motivation